PENGEMBANGAN E-LKPD BERBASIS LITERASI SAINS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V SDN LALADAN - agustin, ina; Muhammad Amrillah Aziz (JPB - Jurnal Pendidikan Biologi, 2024)
Critical thinking is a thinking ability that includes the ability to analyze, draw conclusions, interpret, explain, and self-regulate the thought process that is carried out which is really needed by someone in an effort to solve problems. One way to support and improve critical thinking skills is scientific literacy. Scientific literacy is the ability to use scientific knowledge, identify questions, draw conclusions based on evidence to understand and help make decisions regarding nature and the changes made to nature through human activities. Researchers conducted research entitled "Development of E-LKPD Based on Scientific Literacy to Improve Critical Thinking Ability of Class V Students at SDN Laladan". The aim of this research is to determine the level of validity of E-LKPD based on scientific literacy to improve the critical thinking abilities of fifth grade students at SDN Laladan. This research uses a research and development approach. The model used by researchers is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The data analysis technique used is qualitative and quantitative descriptive data analysis. Quantitative data uses validation sheets from language experts, materials and media. The final conclusion on validity is as follows: (1) the level of validity of linguists is declared very valid with a score of 92%. (2) the level of validity of the material expert is declared very valid with a score of 94%. (3) the level of validity of media experts is declared very valid with a score of 92%. The results of this validation show that the scientific literacy-based E-LKPD that was developed was declared valid and ready to be used to improve the critical thinking skills of fifth grade students at SDN Laladan.